Estilos educativos parentais e desenvolvimento de competências sócio-emocionais em crianças do 1º ciclo do ensino básico - Neves, Carla Sofia Lemos (2018)
O presente estudo tem o objetivo de investigar a relação entre os Estilos Educativos Parentais (EEP) e o desenvolvimento sócio-afetivo em crianças do 1º Ciclo do Ensino Básico. A amostra deste estudo é constituída por (N=106) crianças do 1º Ciclo do Ensino Básico de ambos os sexos, com idades entre os 6 e os 8 anos de idade e respetivos pais. Para a recolha de informação foram aplicados 3 questionários. O Questionário Sócio-Demográfico e o Questionário de Estilos Parentais (Santos & Cruz, 2008) preenchidos pelos pais das crianças e o Questionário de Inteligência Emocional de Bar- On YV (Candeias, Rebelo, Silva & Cartaxo, 2011) respondido pelas crianças. Os resultados do estudo mostram a existência de uma correlação negativa moderada entre o Estilo Permissivo e a dimensão Adaptabilidade. Mostram também que não existem diferenças significativas nas variáveis Género e Habilitações Literárias dos pais quanto a adoção do Estilo Parental. Estes resultados obtidos levam-nos a concluir que não se verifica a existência clara de uma relação entre os Estilos Educativos Parentais e as competências sócio-emocionais das crianças; The Influence of Parental Educational Styles on Socio-Affective Development in Children in the 1st Cycle of Basic Education Abstract: The present study aims to explore the relationship between Parenting Educational Styles and socio-affective development in children in the 1st Cycle of Basic Education. The sample of this study consists of (N=106) children of the 1st Cycle of Basic Education of both sex, aged between 6 and 8 years and respective parents. Three questionnaires were used to collect information. The Socio-Demographic Questionnaire and the Parenting Styles Questionnaire (Santos & Cruz, 2008) completed by the parents and the Bar-On YV Emotional Intelligence Questionnaire (Candeias & Rebelo, 2011) answered by the children. The results obtained lead us to conclude that there is no influence of the Parental Educational Styles on the socio-emotional competences of the children. It was also verified that there were no significant differences regarding the socio-demographic variables Gender and Literary Qualifications of the parents in the adoption of the Parental Style. The results of the study show the existence of a moderate negative correlation between the Permissive Style and the Adaptability dimension. They also show that there are no significant differences in the variables Gender and Literary Qualifications of parents regarding the adoption of the Parental Style. These results lead us to conclude that there is no clear relationship between the Parenting Styles and the socio-emotional competences of the children.